Analysis of Road Pavement Conditions on The Maospati-BTS. Magetan City Road Section Using The Surface Distress Index (SDI) Method - Denastyan Agpenta Putra, Videla; Marleno, Risma; Oetomo, Wateno (Devotion : Journal of Research and Community Service, 2025)
This research evaluates the condition of the pavement on the Maospati - Bts. Magetan City with the Surface Distress Index (SDI) method. The results showed the average value of SDI < 50, indicating that the road condition is in good category with minor damage. The dominant damage types are longitudinal cracks and small holes. Based on the survey results, the estimated maintenance cost required reached Rp. 333,468,376, including patching, slurry seal, and crack sealing works. This study confirms that the SDI method is effective for road maintenance planning and budget allocation in an efficient manner. This strategy not only prolongs the service life of the road but also minimizes long-term maintenance costs. Moreover, sustainable road maintenance practices play a crucial role in supporting regional connectivity and development. Well-maintained roads facilitate smoother transportation, enhance logistics efficiency, and improve access to social and economic services, contributing to inclusive and sustainable growth in Magetan Regency.